The influence of ethnic interest groups on U.S. foreign policy: the case of Armenian diaspora - Gevorgyan, Nora (YSU Journal of International Affairs, 2022)
Of the specific groups that have had an impact on the American foreign policy the ethnic interest groups are the oldest and, arguably, the most influential foreign policy lobby. The present study seeks to understand ethnic interest groups and their influence on U.S. foreign policy. The article addresses how diaspora groups can affect U.S. foreign policy debate and influence the policy abroad, using the Armenian-American diaspora community as a case study. The study examines why and how the Armenian ethnic interest groups influence U.S. policy. The discussion focuses on the specifics of Armenian lobbying institutions in the United States, the main goals and lobbying agendas, as well as mechanisms of influence on the United States’ foreign policy.
Keywords: interest groups; diaspora; Armenian-American community; lobbying; U.S. foreign policy